Generation of a Hetero Spin Complex from Iron(II) Iodide with Redox Active Acenaphthene-1,2-Diimine - Yambulatov, Dmitriy S.; Nikolaevskii, Stanislav A.; Kiskin, Mikhail A.; Kholin, Kirill V.; Khrizanforov, Mikhail N.; Budnikova, Yulia G.; Babeshkin, Konstantin A.; Efimov, Nikolay N.; Goloveshkin, Alexander S.; Imshennik, Vladimir K.; Maksimov, Yurii V.; Kadilenko, Evgeny M.; et al. (Molecules (Basel, Switzerland), 2021)
The reaction of the redox active 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene (dpp-BIAN) and iron(II) iodide in acetonitrile led to a new complex [(dpp-BIAN)FeIII2] (1). Molecular structure of 1 was determined by the single crystal X-ray diffraction analysis. The spin state of the iron cation in complex 1 at room temperature and the magnetic behavior of 1 in the temperature range of 2–300 K were studied using Mossbauer spectroscopy and magnetic susceptibility measurements, respectively. The neutral character of dpp-BIAN in 1 was confirmed by IR and UV spectroscopy. The electrochemistry of 1 was studied in solution and solid state using cyclic voltammetry. The generation of the radical anion form of the dpp-BIAN ligand upon reduction of 1 in a CH2Cl2 solution was monitored by EPR spectroscopy.